DFT Study for Characterization the Biological Activity of New Derivatives of Titanium (IV) Budotitane Complex - Ahmed Abdul Sattar Ali (Journal of Global Pharma Technology, 2018)
The official use of organometallic complexes in chemotherapy dating back to 1969 when cis-platin